Comprehensive and clinical anatomy of the middle ear - Mansour, Salah (Springer)
Most textbooks on otolaryngology and even otology describe the anatomy and embryology of the middle ear in only a limited degree of detail that is inadequate to meet the needs of learners. This book therefore aims to provide otolaryngology residents, otology and neurotology fellows, teachers, and young practitioners with comprehensive, up-to-date information on middle ear anatomy. It will enable those undergoing surgical training to hone their surgical skills and will assist in ensuring that patients receive appropriate management.   The anatomy of the middle ear is explained in easy-to-understand descriptions and exquisitely depicted in more than 100 color photos and numerous helpful color diagrams. Key features of the book are the correlation of clinical situations to the anatomical basis of disease, the simplified explanation of embryology to provide a better understanding of developmental anomalies, and the inclusion of carefully selected CT scans that will assist in the reading of normal anatomy and the identification of pathological features.   Comprehensive and Clinical Anatomy of the Middle Ear is both instructive and enjoyable to read; it provides, within one volume, up-to-date information that the reader would otherwise have to retrieve from many other sources that are often complex and difficult to understand. Temporal bone - Middle ear cavity - Middle ear content - Middle ear compartment - Mastoid - Facial nerve - Eustachian tube.